Three novel species of Russula from southern China based on morphological and molecular evidence - Li, Jing-Wei; Zheng, Jian-Fei; Song, Yu; Yuan, Fa; Qiu, Li-Hong (Phytotaxa, 2019)
Three new species of Russula collected from southern China are proposed based on morphological characters and phylogenetic analysis of internal transcribed spacer (ITS) sequences. Russula bubalina sp. nov. is characterized by cinnamon buff to pink pileus with striate margin, interveined and forked lamellae, basidiospores with warty ornamentations not forming reticulum, hymenial cystidia becoming brown in sulphovanillin (SV) and slender terminal cells in suprapellis. R. pseudobubalina sp. nov. is closely related to Russula bubalina in macro-morphology, but it can be recognized by its unforked lamellae, shorter cheilocystidia, bigger basidia and basidiospores with lower ornamentations. Russula subatropurpurea sp. nov. can be recognized by the purplish brown pileus, mild-tasted and white context changing to light purplish red with FeSO4, white and forking lamellae without lamellulae, long hymenial cystidia becoming brown in SV. Both morphological and phylogenetic analysis consistently confirmed the distinct positions of three new species in subg. Heterophyllidia subsection Heterophyllinae.